Antioxidant Effect of a Probiotic Product on a Model of Oxidative Stress Induced by High-Intensity and Duration Physical Exercise - Maravillas Sánchez Macarro; Vicente Ávila-Gandía; Silvia Pérez-Piñero; Fernando Cánovas; Ana María García-Muñoz; María Salud Abellán-Ruiz; Desirée Victoria-Montesinos; Antonio J. Luque-Rubia; Eric Climent; Salvador Genovés; Daniel Ramon; Empar Chenoll; et al. (MDPI AG, 2021)
This randomized double-blind and controlled single-center clinical trial was designed to evaluate the effect of a 6-week intake of a probiotic product (1 capsule/day) vs. a placebo on an oxidative stress model of physical exercise (high intensity and duration) in male cyclists (probiotic group, n = 22; placebo, n = 21). This probiotic included three lyophilized strains (Bifidobacterium longum CECT 7347, Lactobacillus casei CECT 9104, and Lactobacillus rhamnosus CECT 8361). Study variables were urinary isoprostane, serum malondialdehyde (MDA), serum oxidized low-density lipoprotein (Ox-LDL), urinary 8-hydroxy-2'-deoxiguanosine (8-OHdG), serum protein carbonyl, serum glutathione peroxidase (GPx), and serum superoxide dismutase (SOD). At 6 weeks, as compared with baseline, significant differences in 8-OHdG (Δ mean difference −10.9 (95% CI −14.5 to −7.3); p < 0.001), MDA (Δ mean difference −207.6 (95% CI −349.1 to −66.1; p < 0.05), and Ox-LDL (Δ mean difference −122.5 (95% CI −240 to −4.5); p < 0.05) were found in the probiotic group only. Serum GPx did not increase in the probiotic group, whereas the mean difference was significant in the placebo group (477.8 (95% CI 112.5 to 843.2); p < 0.05). These findings suggest an antioxidant effect of this probiotic on underlying interacting oxidative stress mechanisms and their modulation in healthy subjects. The study was registered in ClinicalTrials.gov (NCT03798821).